Diagnostic accuracy of left atrial remodelling and natriuretic peptide levels for preclinical heart failure. (16th April 2019) - Tsai, Jui‐Peng; Sung, Kuo‐Tzu; Su, Cheng‐Huang; Lai, Yau‐Huei; Kuo, Jen‐Yuan; Yun, Chun‐Ho; Yen, Chih‐Hsuan; Hou, Charles Jia‐Yin; Wu, Tung‐Hsin; Peng, Ming‐Cheng; Hung, Ta‐Chuan; Yeh, Hung‐I; et al.
Abstract: Aims: Left atrial (LA) remodelling is an important predictor of cardiovascular events of heart failure (HF) and atrial fibrillation. Data regarding diagnostic value of LA remodelling on diastolic dysfunction (DD) and preclinical HF remain largely unexplored. Methods and results: We assessed LA dimension (LAD) in 8368 consecutive asymptomatic Asians (mean age: 49.7, 38.9% women) and related such measure to updated American Society of Echocardiography (ASE) DD criteria and newly revised N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) cut‐off (≥125 pg/mL) and HF with preserved ejection fraction criteria incorporating NT‐proBNP and echocardiography parameters by the European Society of Cardiology (ESC). LAD and indexed LAD (LADi) were both inversely correlated with myocardial relaxation e′ and positively associated with indexed LA volume, left ventricular E/e′, and tricuspid regurgitation velocity (all P  < 0.001) and showed significantly graded increase across ASE‐defined 'normal', 'inconclusive', and 'DD' categories (30.9, 34.4, and 36.5 mm; 16.7, 19.1, and 20.6 mm/m 2, for LAD/LADi, both P for trend: <0.001, respectively). Substantial differences of LAD/LADi (31.3 vs. 33.6 mm/16.7 vs. 19.2 mm/m 2, both P  < 0.001) between ESC low and high HF probability using NT‐proBNP cut‐off were also observed. Multivariate linear and logistic models demonstrated that LAD set at 34 mm was independently associated with ASE‐defined diastolic indices, DD existence, and elevated NT‐proBNP (all P  < 0.05). The use of LAD further yielded high diagnostic accuracy in DD (area under receiving operative characteristic curve: 0.77, 95% confidence interval [0.73, 0.80]; negative predictive value: 97.9%) and in ESC‐recommended HF with preserved ejection fraction criteria (area under receiving operative characteristic curve: 0.70, 95% confidence interval [0.65, 0.75]; negative predictive value: 98.7%) with high predictive value in LA remodelling (>34 mL/m 2 ; positive predictive value: 96%) and well‐discriminated ESC‐recommended NT‐proBNP (≥125 pg/mL, LAD: 37 mm) for HF. Conclusions: Single utilization of atrial remodelling is highly useful for ruling out presence of DD and provides practical threshold for identifying preclinical HF based on most updated guidelines.